Perception of risk in the face of climate change in medical students of the University of Medical Sciences of Havana - Adrian Saborit-Rodríguez; Hector Julio Piñera-Castro; Antonio Pupo-Pérez; Dayameylis de la Caridad Macola-Ross; Lutgardo Vera-Aguilera; Hilda Esther Silva-Darcourt (Universidad Médica Pinareña, 2022)
Introduction: the study of the incidence of climate change on human health makes it possible to design and integrate protection and prevention measures.